A historicidade curricular da biblioteconomia na UFPA: o ensino através dos tempos pela análise das ementas de fontes de informação - MACIEL, Bruno Ferreira (2018)
It covers the curricular periods of the Faculty of Library Science of UFPA, aiming to verify the teaching that students of various epochs had in the discipline Information Sources, using their menus, in which documentary proof of the transmitted content. Four curricular periods were identified: 1962 to 1981 (first period), 1982 to 1992 (second period), 1993 to 2008 (third period) and 2009 to present (fourth period). The methods employed were documental research, of qualitative character, where we tried to describe all the changes occurred in the menus of each period up to the present time; and then an analysis was performed based on the data obtained in the description. To this end, similar research was used in other areas of knowledge, as well as a historical contextualization, in order to base the analysis. The results demonstrate the type of teaching used in the four curricular periods, ranging from a training linked to the printed material in the initial periods of the course, to the increasing focus on the electronic medium and the thematic diversification of sources throughout the 21st century.